Evaluation of Subclinical Thyroid Dysfunction in Patients with Type 2 Diabetes Mellitus - Malik, Momna Arooj; Anwar, Muhammad; Haroon, Zujaja Hina; Bibi, Afshan; Munir, Muhammad Usman; Younas, Muhammad (Pakistan Armed Forces Medical Journal, 2024)
Objective: To evaluate subclinical thyroid dysfunction in Type II Diabetes Mellitus patients compared to healthy individuals.Study Design: Cross-sectional study.Place and Duration of Study: Department of Chemical Pathology and Endocrinology, Armed Forces Institute of Pathology, Rawalpindi Pakistan, from July 2021 to May 2022.Methodology: A total of 437 participants, of which 207 had Type II Diabetes Mellitus and 230 had no comorbidities, were included in the study. Thyroid hormone levels were analyzed from serum samples by chemiluminescent method on automated immunoassay analyzer (Advia centaur). Mann-Whitney U test was applied to compare thyroid hormone levels between both groups, and p-value of ≤0.05 was regarded as significant. For risk assessment, frequency and odds ratios, with 95% confidence interval, were determined.Results: There was a significant difference in the medians of Thyroid Stimulating Hormone (p=0.002) and total Triiodothyronine (T3) (p=0.004), while no significant difference was observed in the medians of Free Thyroxine (fT4) (p=0.573) between patients with Type II Diabetes and healthy participants. Diabetic participants had a higher frequency of subclinical thyroid dysfunction than healthy individuals (36% vs 1.3%). Diabetic patients had a greater risk of subclinical thyroid dysfunction than healthy participants (OR: 2.62 vs 0.06) while female participants risk of thyroid dysfunction was higher than males.Conclusion: Risk of subclinical thyroid dysfunction was greater in Type II Diabetes Mellitus patients while subclinical hypothyroidism was the most common thyroid dysfunction.